Deep learning with R cookbook : over 45 unique recipes to delve into neural network techniques using R 3.5.x /: over 45 unique recipes to delve into neural network techniques using R 3.5.x. (2020) - Gupta, Swarna; Ansari, Rehan Ali; Sarkar, Dipayan
No abstract available